The Catholicity of the Church - Dulles, Avery (Oxford Claredon Press, 1985)
Nearly all Christians profess allegiance to the holy catholic church, but the meaning of the term "catholic" is widely disputed. This book investigates the historical use of the word and the various aspects of catholicity. Beginning with the word's divi
Keywords: Church -- Catholicity